Parallel Processing of Facial Expression and Head Orientation in the Macaque Brain - Taubert, Jessica; Japee, Shruti; Murphy, Aidan P.; Tardiff, Clarissa T.; Koele, Elissa A.; Kumar, Susheel; Leopold, David A.; Ungerleider, Leslie G. (The Journal of neuroscience, 2020)
When we move the features of our face, or turn our head, we communicate changes in our internal state to the people around us. How this information is encoded and used by an observer's brain is poorly understood. We investigated this issue using a functional MRI adaptation paradigm in awake male macaques. Among face-selective patches of the superior temporal sulcus (STS), we found a double dissociation of areas processing facial expression and those processing head orientation. The face-selective patches in the STS fundus were most sensitive to facial expression, as was the amygdala, whereas those on the lower, lateral edge of the sulcus were most sensitive to head orientation. The results of this study reveal a new dimension of functional organization, with face-selective patches segregating within the STS. The findings thus force a rethinking of the role of the face-processing system in representing subject-directed actions and supporting social cognition. SIGNIFICANCE STATEMENT When we are interacting with another person, we make inferences about their emotional state based on visual signals. For example, when a person's facial expression changes, we are given information about their feelings. While primates are thought to have specialized cortical mechanisms for analyzing the identity of faces, less is known about how these mechanisms unpack transient signals, like expression, that can change from one moment to the next. Here, using an fMRI adaptation paradigm, we demonstrate that while the identity of a face is held constant, there are separate mechanisms in the macaque brain for processing transient changes in the face's expression and orientation. These findings shed new light on the function of the face-processing system during social exchanges.